Analysis of Using Mind Mapping Methods in Elementary Schools - Hasan, Wilujeng Dewi Latiifah; Puspita, Ari Metalin Ika (International Conference on Elementary Education, 2022)
This study aims to determine the effect of the mind mapping learning model on the learning process of elementary school students. This research method is included in qualitative research with the type of Case Study. The research sample is the fourth grade students of SDN 1 Sumbergedong. Data analysis was done by data triangulation. From the data analysis and discussion, it can be concluded that the use of the mind mapping learning model has an effect on increasing student learning outcomes. The existence of a significant difference indicates that the application of using the mind mapping learning model in class IV has a positive effect on thematic learning outcomes compared to when not using the mind mapping learning model.